1991
DOI: 10.1016/0020-7292(91)90602-2
|View full text |Cite
|
Sign up to set email alerts
|

Availability and use of services for maternal and child health care in rural Nigeria

Abstract: A personal in-home interview was conducted in four rural towns in Nigeria. The aims of the interview were to describe the content of Maternal and Child Health (MCH) care in these rural towns and to assess how patterns of prenatal, delivery and postnatal service use are related to a variety of demographic and socioeconomic variables in the population. Findings from data analysis indicate that services available are deficient in terms of the number of centers and content of care. Variables found to be statistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 19 publications
2
15
0
1
Order By: Relevance
“…The attainment of post secondary education is therefore associated with better utilization of maternal and child health services in health facilities. This finding agrees with the observation from a Jordianian study 14 and also similar studies in Nigeria by Brieger and Luchok, 15 Okafor, 16 Nwakoby 13 and the report of the Nigerian Demographic Health Survey (NDHS) of 2003. 3 In addition, Harrison has shown that female literacy is not only one of the indicators of assessing socio-economic development but is also positively associated with utilization of maternal health services.…”
Section: Subjects Materials and Methodssupporting
confidence: 83%
“…The attainment of post secondary education is therefore associated with better utilization of maternal and child health services in health facilities. This finding agrees with the observation from a Jordianian study 14 and also similar studies in Nigeria by Brieger and Luchok, 15 Okafor, 16 Nwakoby 13 and the report of the Nigerian Demographic Health Survey (NDHS) of 2003. 3 In addition, Harrison has shown that female literacy is not only one of the indicators of assessing socio-economic development but is also positively associated with utilization of maternal health services.…”
Section: Subjects Materials and Methodssupporting
confidence: 83%
“…Most studies discussed elaborately on the determinants of utilization of antenatal care or the pattern of use of antenatal care in a specific state, region or locality. Only few studies considered the determinants of the pattern of antenatal care use at the national level (Okafor, 1991;Nwakoby 1994;Osubor et al 2006). This limited the abilities of most studies to give a representative policy and programme recommendation for Nigeria.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…Watts (1983) referred to them as indigenous towns. In the context of Nigeria, such places are rural towns (Anong and Dipeolu, 1983;Okafor, 1991;Okafor and Okunji, 1996;Adegoke et al, 2010). Voss (2008) notes that the advantages of these developed commercial nodes lead to rapidly rising land values, which are indicative of urbanism in rural areas.…”
Section: The Role Of Rural Towns In Rural Developmentmentioning
confidence: 99%